The Development of Legal Politics in Micro Business Policy of Jombang Regency Government - Moh. Faizin; Surya Anoraga (Audito Comparative Law Journal (ACLJ), 2022)
This paper aims to talk about legal politics, talking about legal products produced by the authorities, whether they hear the aspirations of the community in the process of their formation or are more concerned with the interests or goals of the rulers themselves. Political influence in the formation of law determines the values ​​contained in the law are values ​​that live in a society which is to achieve the goal of the law itself, namely justice. The purpose of the research that the author examines is to describe the formation of the Jombang Regency Regional Regulation Number 9 of 2017 concerning Responsive or Repressive Micro Administration. Based on the process of its formation, the Regional Regulation of Jombang Regency Number 9 of 2017 already contains the principles for the formation of laws and regulations